Athanasius Kircher and Terrestrial Magnetism: The Magnetic Map - Udías Vallina, Agustín (Journal of Jesuit studies, 2020)
Athanasius Kircher paid special attention to magnetism, more specifically terrestrial one, in his work Magnes sive de arte magnetica. Other Jesuits of his time, such as Garzoni and Cabeo, also wrote on this subject. Kircher studied in particular magnetic declination and its possible use to determine geographical longitudes. At his time, this was an important subject for long sea journeys. First, he collected a large number of observations of magnetic declination from different sources in three tables and two lists with a total of 518 values, among them forty-three made by Jesuits. Kircher proposed that a magnetic map could be made based on these observations, but he did not do it. From Kircher's observations a map of magnetic declination has been drawn and it is presented here. Kircher discussed the causes of declination and presented a model for the origin of the magnetic field of the Earth, which differed from that proposed by Gilbert. Kircher finally considered magnetism as a cosmic force with its origin in God.